Gordon Stretton, Black British transoceanic jazz pioneer : a new jazz chronicle - Brocken, Michael; Daniels, Jeff, 1956- (Lexington Books, 2018)
In charting the life and times of Gordon Stretton, this text makes a major contribution to both jazz and popular music studies. By asking historians to re-evaluate the contributions made to the development of jazz by those 'other than' African Americans, it proposes new jazz histories emanating from pathways, influences and encounters.